Kajian Saluran Sungai Akibat Gesekan Limbah pada Aliran Sungai di Bantaran Sungai Kelurahan Toba, Kec. Siantar Selatan - Jhon Sufriadi Purba; Jandri Fan HT Saragi (CERED Indonesia Publishing, 2021)
River pollution is the entry of various substances and non-biodegradable objects that result in contaminated water and loss of function. Besides being a source of various diseases, water pollution also causes flooding. Protecting the river is the same as maintaining survival in the future. Rivers have been the most important part of human life since ancient times. In human evolution, rivers and lakes played an unimaginable role. Rivers are not only important for animals and birds to live, but are also a major source of drinking water. And their environmental value, economic value, and spiritual value touch everyone in the world. In India, people at one time even worshiped rivers as life-giving gods and goddesses. The reason is that every time we search for life, we look for a drop of water first. Rivers carry water and nutrients to areas around the earth. They play a very important role in the water cycle, acting as drainage channels for surface water. Rivers flow almost 75% of the earth's land surface.